PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 10 SOLOKSELATAN TAHUN PELAJARAN 2013/2014 - Welnita, Metri; K, Delsi; Cesaria, Anna (Pendidikan Matematika, 2013)
This research is based on the lack of the studentsâ comprehension of mathematical concepts and the studentsâ low achievement of mathematic at class IX SMPN 10 South Solok academic year 2013/2014. The purpose of this research is to find out whether the studentsâ comprehension ability of mathematical concepts by Quick on the Draw technique is better than Conventional technique does. The design of this research is experimental. The population is the students of class IX SMPN 10 South Solok academic year 2013/2014. Technique of selecting sample is randomly. As a result, IX2 is experiment class and IX1 is control class. The instrument that is used is testing with indicator of concept comprehension ability. The testing contains 9 items with high reliability (0.89). The studentsâ score is analyzed by using t-test one tail. It is found that ttable(1.67) <tcalculated(5.44). It means that the hypothesis is accepted with significant value 95%. This can be concluded that the studentsâ comprehension of mathematical concept by quick on the draw technique is better than the studentsâ comprehension of mathematical concept by conventional technique at IX class of SMPN 10 South Solok academic year 2013/2014.